2000
DOI: 10.1029/1999wr900282
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies reactive tracer test in an aquifer with spatially variable chemical conditions

Abstract: It is hypothesized that stronger adsorption of Pb 2+ to the aquifer sediments causes the Pb-EDTA complex to disassociate to a greater degree than the Cu-EDTA complex. The mass of dissolved Zn-EDTA increased during the first 175 days of the tracer test to 140% of the mass injected, with the increase due to desorption of sewage-derived Zn. Dissolved Ni-EDTA mass remained nearly constant throughout the tracer test, apparently only participating in reversible adsorption reactions. The results of the field experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…The combination of all these reactions leads to rather complicated breakthrough curves that would require more detailed study. An excellent methodology for studying the transport of ETDA-transition metal complexes has recently been published [Davis et al 2000]. A more quantitative analyses of our results would be possible using the Davis et al 2000 approach.…”
Section: Flow-through Column Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The combination of all these reactions leads to rather complicated breakthrough curves that would require more detailed study. An excellent methodology for studying the transport of ETDA-transition metal complexes has recently been published [Davis et al 2000]. A more quantitative analyses of our results would be possible using the Davis et al 2000 approach.…”
Section: Flow-through Column Experimentsmentioning
confidence: 99%
“…The other area that warrants more work is the quantitative determination of the adsorption properties of sediments and soils for picolinate-metal complexes using the "generalized surface complexation modeling approach" that is explained in Davis (2001), and Davis et al (2000). Using this adsorption construct one would develop adsorption constants for particular soils that are akin to thermodynamic stability constants.…”
Section: Summary and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrations of dissolved Mn below an altitude of 11 m were 2 to 3 M ͑data not shown͒, typical of values in the suboxic zone at this distance ͑approximately 300 m͒ downgradient of the sewage-disposal beds. 37,38 Previous comparisons between total dissolved phosphorus concentrations ͑determined by ICPAES͒ and dissolved reactive phosphate concentrations ͑determined colorimetrically͒ have shown that phosphate accounts for all of the dissolved phosphorus, within analytical error. 42,43 The groundwater-chemical features shown in Fig.…”
Section: Groundwater Chemistrymentioning
confidence: 99%